Relationship between Neonatal Asphyxia and Exclusive Breastfeeding with Febrile Seizures in Children in the Bahteramas General Hospital, Southeast Sulawesi - Herman Herman (LPPM STIKes Karya Kesehatan, 2021)
Abstract. According to the Institute of Health Consensus Conference, the occurrence of febrile seizures in infants and toddlers aged 3 – 5 years old is associated with fever without any evidence of infection or intracranial causes. Children with a high body temperature of 380C (rectal temperature) are subject to febrile seizure. About 90% of febrile seizures sufferers are children under five years. In Indonesia, the prevalence of febrile is estimated to 2 – 4% while the data shown in Bahteramas Hospital during the past three years indicated an increased incidence of febrile seizures in as many as 17, 87, and 149 patients respectively in 2013, 2014, and 2015. The present study aimed to understand the relation between neonatal asphyxia and exclusive breastfeeding to the incidence of febrile seizures in children at Bahteramas Hospital, Southeast Sulawesi. This study is an analytical study with a case-control approach. The population of the study was mothers whose child suffering from febrile seizures in Mawar room from January to Mei 2016 as many as 105 patients, later 60 patients were enrolled in the study using an accidental sampling technique. The statistical analysis was made using an odds ratio and binary logistic regression. The results show that neonatal asphyxia (OR=4.750) and exclusive breastfeeding ( OR=4.929) are associated with the incidence of febrile seizures in children. It is suggested for mothers to prevent their toddlers from asphyxia and promoting a 6-month exclusive breastfeeding practice to naturally boost immunity from febrile seizure.